Systemic factors for enhancing intersectoral collaboration for the operationalization of One Health: a case study in India - Sandul Yasobant; Walter Bruchhausen; Deepak Saxena; Timo Falkenberg (BMC, 2021)
Abstract Background One Health is a collaborative, multisectoral, and transdisciplinary approach-working at the local, regional, national, and global levels-with the goal of achieving optimal health outcomes recognizing the interconnection between people, animals, plants, and their shared environment. Operationalization of the One Health approach is still unclear for various local health systems with their respective targets. In this scenario, the empirical study of intersectoral collaboration between the human and animal health systems provides an opportunity to investigate the appropriate strategies and their enabling factors at the local health system level. Thus, this study documented and validated the innovative strategy for intersectoral collaboration, focusing on effectual prevention and control of zoonotic diseases with its enabling factors for a city in western India, Ahmedabad. Methods This case study was conducted in three phases: phase I (qualitative data collection, i.e., vignette interview), phase II (quantitative data collection through modified policy Delphi), and phase III (participatory workshop). The vignette data were handled for content analysis, and the Delphi data, like other quantitative data, for descriptive statistics. The participatory workshop adapts the computerized Sensitivity Model® developed by Vester to analyse the health system dynamics. Result Out of the possible 36 strategies, this study validated the top 15 essential (must-have) and five preferred (should-have) strategies for the study area. For operationalization of the One Health approach, the enabling factors that were identified through the systems approach are micro-level factors at the individual level (trust, leadership, motivation, knowledge), meso-level factors at the organizational level (human resource, capacity-building, shared vision, decision-making capacity, laboratory capacity, surveillance), macro-level factors at the system level (coordinated roles, relationships, common platform), and external factors outside of the system (guidelines/policies, community participation, a specific budget, political will, smart technology). Discussion This study reveals that the micro-level factors at the individual level are potential levers of the health system. More attention to these factors could be beneficial for the operationalization of the One Health approach. This study recommends a systems approach through a bottom-up exploration to understand the local health system and its enabling factors, which should be accounted for in formulating future One Health policies.